2015 IEEE International Electric Machines &Amp; Drives Conference (IEMDC) 2015
DOI: 10.1109/iemdc.2015.7409218
|View full text |Cite
|
Sign up to set email alerts
|

Identification of design rules for interior PM motors with different cooling systems

Abstract: The conventional scaling rules for the optimal design of electric machines are best suited for naturally cooled machines with stator winding current densities less than 4A/mm 2 . In this paper, through a comprehensive sensitivity analysis, first, it is demonstrated that the correlations between some geometric variables and the performance metrics of interior permanent magnet (IPM) motors vary significantly with respect to the stator winding current density. For this purpose, three current densities are selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A case of particular concern pointed out by numerous studies [8][9][10][11] is in traction applications, where the motor is most likely to operate far away from its rated torque and nominal speed. This is whereas the correlation between the main design variables and motor performance metrics, can be significantly affected by the machine's level of ampere loading and magnetic core saturation [12]. This accentuates the challenges in the design of electric motors with intermittent operating cycles where an optimal design is to maintain high performance under various loading conditions.…”
mentioning
confidence: 96%
“…A case of particular concern pointed out by numerous studies [8][9][10][11] is in traction applications, where the motor is most likely to operate far away from its rated torque and nominal speed. This is whereas the correlation between the main design variables and motor performance metrics, can be significantly affected by the machine's level of ampere loading and magnetic core saturation [12]. This accentuates the challenges in the design of electric motors with intermittent operating cycles where an optimal design is to maintain high performance under various loading conditions.…”
mentioning
confidence: 96%
“…This paper contains further contribution through a parallel investigation of the relations between the geometric design parameters and the performance metrics of interior PM (IPM) motors for a wide range of ampere-loading levels determined by the machine's cooling system. 20 This is accomplished through a systematic sensitivity analysis and large scale design optimization. Accordingly, it will be demonstrated that one set of design rules, such as those derived in, 19 cannot be generalized to all three classes of cooling systems.…”
Section: Introductionmentioning
confidence: 99%